MAIUS-1 - Vehicle, Subsystems Design and Mission Operations - Stamminger, Andreas; Ettl, Josef; Grosse, Jens; Hörschgen-Eggers, Marcus; Jung, Wolfgang; Kallenbach, Alexander; Raith, Georg; Saedtler, Wolfram; Seidel, Stephan; Turner, John; Wittkamp, Markus (ESA Communications, 2015)
In November 2015, the DLR Mobile Rocket Base will launch the MAIUS-1 rocket vehicle at Esrange, Northern Sweden. The MAIUS-A experiment is a pathfinder atom optics experiment. The scientific objective of the mission is the first creation of a Bose-Einstein Condensate in space and performing atom interferometry on a sounding rocket. MAIUS-1 comprises a two-stage unguided solid propellant VSB-30 rocket motor system. The vehicle consists of a Brazilian S31 motor as 1st stage, a S30 motor as 2nd stage, a conical motor adapter, a despin module, a payload adapter, the MAIUS-A experiment consisting of five experiment modules, an attitude control system module, a newly developed conical service system, and a two-staged recovery system including a nosecone. In contrast to usual payloads on VSB-30 rockets, the payload has a diameter of 500 mm due to constraints of the scientific experiment. Because of this change in design, a blunted nosecone is necessary to guarantee the required static stability during the ascent phase of the flight. This paper will give an overview on the subsystems which have been built at DLR MORABA, especially the newly developed service system. Further, it will contain a description of the MAIUS-1 vehicle, the mission and the unique requirements on operations and attitude control, which is additionally required to achieve a required attitude with respect to the nadir vector. Additionally to a usual microgravity environment, the MAIUS-1 payload requires attitude control to achieve a required attitude with respect to the nadir vector.